Short Term Outcome of Urethroplasty for Distal Hypospadias with Interrupted Suture Compared to continuous Suture (Journal of Paediatric Surgeons of Bangladesh, 2013)
Background: Hypospadias is one of the most common congenital anomalies, occurring approximately 1in 200 to 1in 300 live birth. Urethrocutaneous fistula (U-C fistula), and meatal stenosis are the most common complication of hypospadias surgery. To reduce these complications there are different surgical procedures. Snodgrass technique is now the popular technique for its low complication rate and better cosmetic outcome. Objective: To explore the short term outcome of interrupted suture compared to continuos suture in snodgrass technique urethroplasty for distal penile hypospadias. Method: It was a randomized control trial study carried out in the department of Paediatric surgery, BSMMU during the period of June 2008 to September 2009. 32 patients with distal penile hypospadias were selected according to set inclusion and exclusion criteria. Subjects who included in the study were randomly distributed in two groups. In group A odd number of patients and in group B even number of patients were included for randomization. Group A (interrupted suture) was treated as interventional group and Group B (continuous suture) as control group. Penile stent was removed on 8th and 10th POD after snodgrass technique of urethroplasty in coronal and subcoronal hypospadias respectively and observed for 4 weeks for two common complications- Urethrocutaneous fistula (U-C fistula), and meatal stenosis. Unpaired t test, Fishers exact test were used to see the level of significance. Result: In group A out of 16 subjects; 2 subjects (12.5%) develop Urethrocutaneous fistula and 1 subject (6.3%) had developed meatal stenosis. In group B out of 16 subjects 6 subjects (37.5%) had developed Urethrocutaneous fistula and 3 subjects (18.8%) developed meatal stenosis. Conclusion: Urethrocutaneous fistula (U-C fistula), and meatal stenosis are the most common complication of hypospadias repair and the occurrence of these two complications are less in interrupted suture than that of continuous suture in Snodgrass technique urethroplasty for distal hypospadias. DOI: http://dx.doi.org/10.3329/jpsb.v2i1.15160 Journal of Paediatric Surgeons of Bangladesh (2011) Vol. 2 (1): 26-30